Electrical model to predict current-voltage behaviours of lithium ferro phosphate batteries using a transient response correction method - Low, W.Y.; Aziz, J.A.; Idris, N.R.N.; Saidur, Rahman (Journal of Power Sources, 2013)
Lithium ferro phosphate (LiFePO 4) batteries are stable in terms of their thermal and chemical characteristics and have a high potential for wide use in the future. A battery model that predicts current-voltage (I-V) performance with high accuracy is vital for circuit designers so they can design circuits to control the usage of the battery and improve its runtime and its safety during use. In this paper, a battery model with two resistance- capacitance (RC) parallel networks is used for modelling and the values for parameters are divided into two sets; one for loaded conditions and the other for unloaded conditions. A methodology of transient response correction is proposed for formulating the parameters of the loaded condition. The steps for parameter extraction are discussed and the proposed battery model is validated using data from several experiments. The comparison between experiment and simulation results shows that the proposed model is capable of predicting I-V performance of the battery with very little error.